The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/2277-9175.120871
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between intra-operative electrolyte abnormalities (sodium and potassium) with post-operative complications of coronary artery bypass surgery

Abstract: Background:Generally, the electrolyte abnormalities are seen in many hospitalized patients, and this problem increases in ones with heart diseases. The purpose of this study is determination of the prevalence of electrolyte abnormalities during the coronary artery bypass surgery (CABG) and detecting the relationship between these abnormalities with the complications after the surgeries.Materials and Methods:This is a cross-sectional study, which is done in Chamran hospital, the medical and educational center o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…This suggests that potassium levels are not only crucial for postoperative gastrointestinal activation after abdominal surgery, but also have an influence on systemic recovery after surgery in general. The type of urinary diversion (continent vs. incontinent) had no impact on length of hospital stay in our study, whereas an association between continent ileal neobladder and longer hospital stay had been reported before [11].…”
Section: Discussioncontrasting
confidence: 73%
“…This suggests that potassium levels are not only crucial for postoperative gastrointestinal activation after abdominal surgery, but also have an influence on systemic recovery after surgery in general. The type of urinary diversion (continent vs. incontinent) had no impact on length of hospital stay in our study, whereas an association between continent ileal neobladder and longer hospital stay had been reported before [11].…”
Section: Discussioncontrasting
confidence: 73%
“…These results are comparable with the previous study of Bagheri 2013 reported that imbalance in potassium and sodium levels during cardiac surgery can cause postoperative complications. 15 Polderman 2004 reported that patients undergoing cardiac surgery with extracorporeal circulation are at high risk of electrolyte depletion. 16 Dieter conclude that preoperative diuretic therapy major cause of hypokalemia postoperatively.…”
Section: Discussionmentioning
confidence: 99%